Song Quest - Roberts, Katherine 1962. (New York : Scholastic Inc., 2002)
Stranded, alone, and far from home, Rialle and Kherron struggle against the powers of darkness.
"First published in the United Kingdom in 1999 by Element Children's Books, Shaftesbury, Dorset"--Verso t.p.
G5
Keywords: Good and evil -- Juvenile fiction